Variation induction of Glycine max through low dose gamma irradiation produces genetic and physiological alteration as source of tolerant variants in waterlogging conditions (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Saputro TB, Muslihatin W, Wahyuni DK, Nurhidayati T, Wardhani FO, Rosalia E. 2019. Variation induction of Glycine max through low dose gamma irradiation produces genetic and physiological alteration as source of tolerant variants in waterlogging conditions. Biodiversitas 20: 3299-3308. Soybean (Glycine max L.) is the main food commodity that contains high proteins, oils, and carbohydrates. Waterlogging is considered as the dominant factor and major constraint responsible for the decrements of soybean production in Indonesia. The development of promising G.max that tolerates waterlogging is essentially needed. In this study, induction of variation was conducted by gamma rays irradiation with doses of 25Gy, 50Gy, 75Gy, and 100Gy. The mutant or variants lines were then selected under waterlogging conditions with 100%, 150%, 200%, and 250% of field capacity. The results showed that, in 250% waterlogging condition, plants irradiated with 25Gy shows the best performance in amount of roots, adventitious roots and number of pods parameters, while plants irradiated with 50Gy have the highest growth indicated by amount of root nodules, plant heights, dry weights, leaf area, and chlorophyll contents. The genotypes then were assayed by the Inter Simple Sequence Repeats (ISSR) to confirm that the mutants differ compared to its wild type. Out of 10 ISSR primers, seven primers showed polymorphic patterns. The best primer to differentiate the mutant lines and its wild type is primer ISSR1 [ (AC)8G] that able to generate the highest level of polymorphism with 44.0%. The comparison of protein profiles among the mutant lines showed that proteins with molecular weight 53,78 KDa; 43,12 KDa; and 20,62 Kda are all overexpressed for plants irradiated at 25Gy and treated with 250% waterlogging stress. All those three proteins are predicted as 1-amino cyclopropane-1-carboxylate synthase (ACS), Alcohol-dehydrogenase (ADH), and Superoxide dismutase (SOD) respectively.
Keywords: ACS, ADH, gamma rays, Glycine max, ISSR, MI, PIC, SDS-PAGE, SOD, waterlogging